Penerapan Layanan Bimbingan Kelompok Teknik Homeroom untuk Meningkatkan Pemahaman Bahaya Seks Bebas - Sofiatul Lailiyah; Noer Faqih; Siti Rahayu (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2019)
This research was conducted in class VIIIB of Ahlul Irfan Langkap Bangsalsari Jember. Type this research is quantitative by using a pre-experimental approach with the design of one group pretest-posttest. The population in this study were all students of class VIIIB SMP Ahlul Irfan Langkap Bangsalsari Jember with sampling taken using purposive sampling. Data collection techniques in this study were to use documentation, interviews and questionnaires which were then distributed and analyzed using the Wilcoxon test. Based on the results of research on the understanding of the dangers of free sex there is an increase in the provision of group guidance (Homeroom technique for the understanding of students of class VIIIB Ahlul Irfan Capture Bangsalsari Jember 2018-2019 school year. It is seen from the Z count (0.016)> Z table (0.05) which means Ho was rejected and Ha was accepted. Keywords: Homeroom Technique, the dangers of free sex